Mindset, Moral Choice and Sin in the Anthropology of John Chrysostom. By Raymond Laird - Verhoeff, Maria (The journal of theological studies, 2014)
The fifteenth volume of the monograph series published by the Centre for Early Christian Studies of the Australian Catholic University is a reworked Th.D. dissertation (University of Sydney, 2008) by Raymond Laird on the dominant role of the γνώμη, the mindset, in John Chrysostom’s anthropology., The first part of the book (chs. 2–6) presents a thorough examination and analysis of a careful selection of exegetical texts from Chrysostom’s oeuvre. Here Laird convincingly counters the tendency in patristic scholarship to overemphasize the role of προαίρεσις, moral choice, in Chrysostom. According to Laird, Chrysostom treats moral choice as an expression of the mindset, rather than as the primal controlling factor in one’s acting.